2019
DOI: 10.1007/s10064-019-01496-0
|View full text |Cite
|
Sign up to set email alerts
|

Shear velocity-based uncertainty quantification for rock joint shear strength

Abstract: The shear strength of rock joints is an important property required in order to analyze the stability of rock slopes and tunnels. However, estimation of the shear strength of rock joints for in situ conditions is a complex task due to various influencing factors present in the field. Among these factors, the shear velocity or the shear displacement rate along the rock joints are important parameters which are relatively less studied since their effect is considered to be of second order compared to other facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, the joint shear strength estimated under low shear rates in the laboratory cannot be applied to field conditions. To study the impact of high shear rates on shear performance, Tiwari 55 developed a probabilistic method to estimate the in-situ shear strength of joints under high displacement rate conditions. That study found that the shear strength of structural plane decreases with increasing shear rate, and this dependence is more significant under low-density rock and high confining stress conditions.…”
Section: Relative Workmentioning
confidence: 99%
“…However, the joint shear strength estimated under low shear rates in the laboratory cannot be applied to field conditions. To study the impact of high shear rates on shear performance, Tiwari 55 developed a probabilistic method to estimate the in-situ shear strength of joints under high displacement rate conditions. That study found that the shear strength of structural plane decreases with increasing shear rate, and this dependence is more significant under low-density rock and high confining stress conditions.…”
Section: Relative Workmentioning
confidence: 99%
“…e mining waste includes the stripping and waste rock (including coal gangue) produced in the process of mining, as well as the tailings discarded in the process of mineral dressing [1][2][3][4][5][6]. A large amount of mining solid waste as well as the complicated treatment has become one of the issues that should be addressed for environmental protection [4,[7][8][9][10][11][12]. e massive accumulation of mining waste can cause pollution of the land, causing disasters such as landslides and mudslides.…”
Section: Introductionmentioning
confidence: 99%
“…e debris and tailings formed by the weathering of waste rock are either washed by water into the water body, dissolved and penetrated into the groundwater, or blown into the atmosphere by the wind, polluting the environment with water and gas as the medium [13][14][15][16]. ese mining waste materials not only take up a lot of land but also directly pollute the environment and threaten the safety of people's lives, since some of these wastes contain highly toxic elements, such as arsenic and cadmium, and radioactive elements, which are harmful to human health [1,2,4,[7][8][9]. Tailings have the characteristics of fine particles, small weight, large surface area, being easy to run away in contact with water, and being easy to fly when exposed to wind.…”
Section: Introductionmentioning
confidence: 99%
“…The strength, deformation, and stability of the rock mass are mainly controlled by the joint surface [11][12][13][14]. As a natural defect formed in the long geological process, joints exist in the rock mass with complex geometric shapes, scales, and filling forms, which seriously affect and restrict the mechanical behavior and deformation, and failure characteristics of the rock mass [15][16][17][18][19][20]. Large-scale rock mass-engineering disasters are mainly caused by the expansion, evolution, and penetration of existing joints [4,12,21].…”
Section: Introductionmentioning
confidence: 99%